2001
DOI: 10.1063/1.1370558
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution x-ray crystal spectrometer/polarimeter at torus experiment for technology oriented research-94

Abstract: A high-resolution x-ray polarimeter has been installed at the torus experiment for technology oriented research ͑TEXTOR-94͒. The instrument consists of two spectrometers in Johann geometry, utilizing the dependence of Bragg reflection on the polarization. The dispersion plane of the so-called horizontal spectrometer coincides with the midplane of the tokamak, whereas the dispersion plane of the so-called vertical spectrometer lies perpendicular to the midplane of the tokamak. Both spectrometers operate with cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…Various Ne IX and Ne X transitions are identified and listed in the table. The experimental results have shown that the calculated spectral resolution (λ/∆λ) approximates 379 with ∆λ being the full-width at half-maximum (FWHM) [13] . Fig.…”
mentioning
confidence: 93%
“…Various Ne IX and Ne X transitions are identified and listed in the table. The experimental results have shown that the calculated spectral resolution (λ/∆λ) approximates 379 with ∆λ being the full-width at half-maximum (FWHM) [13] . Fig.…”
mentioning
confidence: 93%
“…It is well known that the focusing spectrograph is capable of recording highly resolved spectra with a significantly higher sensitivity [10][11][12] . As an example of such a device, the Johann configuration spectrometer [13,14] can obtain a high luminosity, good spatial resolution, and slightly lower spectral resolution, and has been used from the source on the Rowland circle experiments. In a von Hamos crystal spectrometer setup [15] the energy resolution depends on the size of the effective source.…”
mentioning
confidence: 99%
“…In recent years, x-ray spectroscopy has been further developed on other MFE devices, such as LHD [244][245][246][247] , TEXTOR [248][249][250][251] , and NSTX [252][253][254][255] . The LHD spectrometer 244 employs a quadrangular crystal holder with four cylindrically bent quartz crystals, allowing the instrument to be tuned for the observation of the He-like ion spectra of argon, titanium, chromium, and iron.…”
Section: -242)mentioning
confidence: 99%
“…Accurate measurements of the argon ion charge state distribution as a function of density from TEXTOR discharges with and without neutral beam injection documented large deviations from coronal equilibrium due to charge exchange recombination during neutral-beam injection 249 .…”
mentioning
confidence: 99%